Student Independence in Studying at Islamic Boarding Schools - Mala, Muhammad Yusuf; Nurus Sa'adah (ILIN Institute, 2023)
In education the need for independent learning in students, independence has its own goals to assess how active students are in learning both in formal education and non-formal education. Islamic boarding schools have classical and non-classical classes, with these classes the learning becomes varied. Learning independence will be formed from the attention given by parents, Islamic boarding school caretakers, asatidz. This attention will later make student learning independence better and will get good results too. Islamic boarding schools are currently developing to keep up with the times such as giving birth to madrasas that have general knowledge, with this in mind it will continue with Law number 20 of 2003 in chapter II article 3. Islamic boarding schools are also protected by Law number 18 of 2019 which provides recognition in the form of recognition of equality to pesantren graduates. The need for attention given to students in order to produce quality students.